2013
DOI: 10.1007/s12178-013-9168-9
|View full text |Cite
|
Sign up to set email alerts
|

Update on the female athlete triad

Abstract: Updated prevalence estimates of all 3 components of the Female Athlete Triad, a syndrome characterized by low energy availability, functional hypothalamic amenorrhea, and osteoporosis, is low (0 %-16 %), however, estimates of 1 or 2 concurrent components approach 50 %-60 % among certain athlete groups. Recent research identifies components of the Triad among female adolescent athletes, particularly those participating in leanness sports, such as endurance running. This is alarming, as adolescents require adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 102 publications
1
43
0
3
Order By: Relevance
“…22 Among distance runners, concern about energy deficits is heightened because of the prevalence of eating disorders and the female athlete triad, both of which may contribute to bone loss and bone injury. 11,[23][24][25][26] We did not formally evaluate the female athlete triad, although the number of reported fractures and stress fractures is small. Nevertheless, primary prevention of disordered eating is an important strategy for risk reduction related to compromised bone density and other physiologic health consequences of inadequate energy intake.…”
Section: Overuse and Ntl Injuriesmentioning
confidence: 99%
“…22 Among distance runners, concern about energy deficits is heightened because of the prevalence of eating disorders and the female athlete triad, both of which may contribute to bone loss and bone injury. 11,[23][24][25][26] We did not formally evaluate the female athlete triad, although the number of reported fractures and stress fractures is small. Nevertheless, primary prevention of disordered eating is an important strategy for risk reduction related to compromised bone density and other physiologic health consequences of inadequate energy intake.…”
Section: Overuse and Ntl Injuriesmentioning
confidence: 99%
“…10,15,21,22,24,31 The prevalence of anovulation and luteal phase deficiency has not been evaluated in adolescent athletes but ranges from 5.9% to 30% in adult athletes. 11 Amenorrheic adolescent athletes have a significantly lower BMD than eumenorrheic adolescent athletes or sedentary controls. 13,31,33 Some studies have found that athletes with menstrual irregularities are as much as 3 times more likely to sustain bone stress injury and other musculoskeletal injury than are eumenorrheic athletes, 26, 34-36 but this finding has not been consistent.…”
Section: Menstrual Functionmentioning
confidence: 96%
“…In high schoolaged female athletes, the prevalence of 2 concurrent components of the triad is 4% to 18% and of any 1 component is as high as 16% to 54%. [9][10][11][12][13][14][15] Education of pediatricians, who are most likely to encounter adolescents with triad-related disorders, is especially important. Unfortunately, a 2009 study found that only 20% of pediatricians were able to correctly identify all 3 components of the triad, compared with 50% of family medicine physicians and 41% of orthopedic surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…RED-S is an interrelation between sufficient energy intake, menstrual function, and bone mineral density. Female athletes are at risk for this condition, where energy restriction can lead to amenorrhea and osteoporosis, cardiovascular effects, stress fractures, and musculoskeletal injuries [6]. Screening for RED-S and disordered eating is commonly provided for female athletes entering college, especially in schools that employ a sports Registered Dietitian who can provide appropriate education [7].…”
Section: Introductionmentioning
confidence: 99%